Atrazine nanoencapsulation improves pre-emergence herbicidal activity against Bidens pilosa without enhancing long-term residual effect on Glycine max - Preisler, Ana C; Pereira, Anderson ES [UNESP]; Campos, Estefânia VR [UNESP]; Dalazen, Giliardi; Fraceto, Leonardo F [UNESP]; Oliveira, Halley C (Wiley, 2019)
BACKGROUND: Poly(ϵ-caprolactone) nanocapsules (NC + ATZ) are an efficient carrier system for atrazine and were developed as an alternative to reduce the harmful environmental effects of this herbicide. Here, we analyzed the pre-emergence herbicidal activity of NC + ATZ against Bidens pilosa and evaluated its residual effect on soybean plants after different periods of soil treatment with the formulations. RESULTS: In contrast to non-nanoatrazine, NC + ATZ treatment led to very high mortality rates of B. pilosa seedlings even after a tenfold dilution, which suggests that atrazine nanoencapsulation improved its pre-emergence herbicidal activity. In a short-term assay (17 days), soil treatment with all atrazine-containing formulations resulted in intense toxicity to soybean plants. NC + ATZ at 200 g ha−1 had the same inhibitory effects on the physiological and growth parameters of soybean plants compared with non-nanoatrazine at 2000 g ha−1, which suggests that atrazine nanoencapsulation increased the short-term residual effect of the herbicide. In a long-term assay (60 days), a gradual recovery of soybean plants from atrazine phytotoxicity was observed. When comparing the effects of nano- and non-nanoatrazine at the same concentrations, the growth and physiological parameters of soybean plants were mainly affected to the same extent. This indicates that encapsulation of atrazine into poly(ϵ-caprolactone) nanocapsules did not enhance the long-term residual effect of the herbicide on soybean. CONCLUSION: NC + ATZ could be applied for efficient weed control without additional phytotoxicity to susceptible crops compared with non-nanoatrazine, provided that a safe interval is respected from atrazine application to sowing. © 2019 Society of Chemical Industry.
Keywords: hairy beggarticks; nanocapsules; nanotechnology; phytotoxicity; soybean; weeds